Comparative Analysis of the Greenhouse Gas Emissions from Road Transport in The Metropolitan Cities of Turkey - Abdullah Oktay Dündar (Doğal Afetler ve Çevre Dergisi)
In this study, the amount of greenhouse gas emissions from road transport belonging to the metropolis in Turkey in 2010 and 2019 were calculated using the Tier 1 method developed by the IPCC. According to the results, while the total amount of greenhouse gas emissions in 30 metropolitan cities in 2010 was 43,403 Gg CO2 equivalent, it increased in 2019 and reached 70, 271 Gg CO2 equivalent. Between 2010 and 2019, the total amount of greenhouse gas emissions increased by 61.90%. The cities of Istanbul, Ankara, İzmir in total greenhouse gas emissions, Denizli, Mersin, Muğla in terms of greenhouse gas emissions per capita, Mardin, Kocaeli, Diyarbakır in terms of greenhouse gas emissions per vehicle, and Istanbul, Kocaeli and İzmir in terms of greenhouse gas emissions per km2. are in the top 3 places. Both in 2010 and 2019, Istanbul, Ankara, Izmir, Bursa, Mersin, Antalya, Konya and Kocaeli have values above the average emission amount. With priority measures to be taken in these cities, the total amount of emissions in our country can be reduced significantly. On the other hand, in cities in our eastern region such as Mardin, Van and Şanlıurfa, the speed of increase in emissions is much higher than that of other cities. In the study, metropolitan cities were compared according to alternative transportation options and infrastructures and it was determined that other options, except rail, were effective in reducing the emission rate.